Do customers evaluate the competence of SME retailers and retail chains differently in the context of online product presentations? - Mennekes, Theresia; Röding, Tobias; Wagner, Gerhard; Schramm-Klein, Hanna (International journal of retail & distribution management, 2023)
PurposeThe purpose of this paper is to explore the extent to which customers evaluate inferior product presentations on a local shopping platform based on the retailer (small and medium-sized enterprise [SME] vs retail chain).Design/methodology/approachThe authors conducted a between-subject online study (N = 728) with a 2 (SME vs retail chain) x 2 (high vs low-quality product presentation) between-subject experimental design. The authors conducted several analyses of variance to analyze the hypotheses and analyses of covariance for a mediating effect.FindingsThis study's results show that customers tend to overlook inaccuracies from a retail chain more often than they overlook inaccuracies from SME retailers. The authors show that the perceived competence of the retailer mediates the impact of the retailer's quality on customer purchasing intentions, not only for the presented product but also for the retailer itself.Practical implicationsBased on this study's results, the authors give implications for retailer cross-channel strategies and hint at the importance of emphasizing the retail size.Originality/valueThis paper provides important contributions to the literature on resource-advantage theory by explaining that consumers perceive quality differences within product presentations on online shopping platforms differently with regard to retail chains vs SME retailers. Moreover, the information processing theory helps to provide a theoretical foundation concerning differences in online store quality (via engineered low- vs high-quality product presentations in this study).